“Exogeny” and “tolerance”: the double role of the print media in the institutionalization of homosexuality in post-colonial southern Mozambique (1975-2007) - Miguel, Francisco Paolo Vieira (Revista de Antropologia, 2023)
In this article, I investigate historiographically and ethnographically, four large-circulation Mozambican newspapers between the years 1975 and 2007, in order to understand how the country's press has treated the issue of homosexuality since independence. It is concluded that the local press, by publicizing the homosexuality of foreigners and not engaging in hate speech, reinforced the idea of the exogeny of homosexuality in Africa and, unlike other neighboring African nations, produced an environment of tolerance towards the issue in Mozambique.